2022
DOI: 10.1039/d2py00407k
|View full text |Cite
|
Sign up to set email alerts
|

Customizable nano-sized colloidal tetrahedra by polymerization-induced particle self-assembly (PIPA)

Abstract: Colloidal molecules (CMs) are colloidal clusters with molecule-like symmetry and architecture, generated from the self-assembly of nanoparticles with attractive patches. However, large-scale preparation of patchy nanoparticles remains challenging. Here, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…S3f †). It should be noted that nanoparticles with tetrahedral surface structure are rather rare 19 and have not been observed in our previous works on solution self-assembly of ABC triblock terpolymers. 20,23 These particles are of particular interest for higher hierarchical self-assembly.…”
Section: Controlling the MCM Shapementioning
confidence: 73%
See 1 more Smart Citation
“…S3f †). It should be noted that nanoparticles with tetrahedral surface structure are rather rare 19 and have not been observed in our previous works on solution self-assembly of ABC triblock terpolymers. 20,23 These particles are of particular interest for higher hierarchical self-assembly.…”
Section: Controlling the MCM Shapementioning
confidence: 73%
“…Very recently, this concept was adapted to the polymerization-induced particle assembly of AB diblock micelles into triblock terpolymer clusters with high fraction of tetrahedral nanostructures. 19 We previously demonstrated that a hierarchical self-assembly process by step-wise solvent exchange allows the formation of very homogeneous MCMs with predictable morphology thereby gaining access to patchy and striped spheres, cylinders, sheets and polymersomes. [20][21][22][23][24] However, this technique is usually accompanied by a special preparation protocol and requires excessive amounts of solvents.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, the PISA method was developed. It can directly prepare diblock copolymer nanoparticles with controllable morphology [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , and high concentration (50 wt%), offering the advantages of simplicity, efficiency, and repeatability. With the advancement of PISA, initiation is no longer limited to thermal methods, leading to the emergence of greener and more energy-efficient initiation mechanisms and supportive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of block copolymers enables the preparation of nanoparticles with various morphologies, such as spheres [1] , [2] , worms [1] , [2] , [3] , vesicles [2] , [4] , [5] , [6] , [7] , [8] , lamellae, spongosomes [9] , [10] , [11] , [12] , [13] , hexosomes [14] , cubosomes [14] , Janus particles [15] , [16] , colloidal molecules [15] , [16] , [17] , [18] , and many others [19] , [20] , which find wide-ranging applications including biomedicine [21] , [22] , [23] , [24] , [25] , batteries [26] , [27] , [28] , coatings [29] , [30] , [31] , Pickering emulsions [32] , [33] , [34] , [35] , catalysis [36] , [37] , [38] , and so forth [39] , [40] , [41] , [42] , [43] , [44] . Traditional self-assembly requires an initiation polymerization to obtain block copolymers, followed by a replacement of solvents.…”
Section: Introductionmentioning
confidence: 99%